Why those who shovel are silent : a history of local archaeological knowledge and labor - Mickel, Allison (University Press of Colorado, 2021)
"Years of ethnographic work with current and former workers at two Middle Eastern archaeological sites combined with archival research. Describes the knowledge that locally-hired laborers possess about artifacts, excavation methods, and interpretation, showing that archaeological workers are experts-and are paid by archaeologists to pretend to be less knowledgeable"--